A comparative study on the effect of sodium valproate therapy on liver enzyme levels in children with seizure disorder compared to other antiepileptic drugs - Sri M., Swathi; S., Chidambaranathan (International Journal of Contemporary Pediatrics, 2025)
Background: Sodium valproate is a commonly prescribed antiepileptic drug known for its effectiveness in controlling seizures in pediatric patients but is also associated with concerns over altered liver enzyme levels and rarely hepatotoxicity. Comparisons with other antiepileptic drugs are essential to understand their relative impacts on hepatic function in children with seizure disorder. Methods: A prospective study was conducted in the department of paediatrics at the Government Cuddalore Medical College Hospital over a one-year period, enrolling children aged 1 to 12 years diagnosed with seizure disorder and on sodium valproate, phenytoin or levetiracetam therapy. Liver function was assessed by measuring serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), and alkaline phosphatase (ALP) measured at baseline and after 12 months. Inclusion and exclusion criteria ensured well-defined cohorts, and enzyme levels were measured using standard clinical laboratory techniques. Data was collected via structured proforma and analysed by SPSS version 25 software. Results: Among the 40 recruited children, those receiving sodium valproate demonstrated significant elevations in SGOT, SGPT, and ALP levels after one year of therapy. In contrast, children receiving levetiracetam showed increased ALP levels only, while no significant changes were observed in the phenytoin group. Statistical analysis confirmed the significance of these findings, underscoring sodium valproate’s stronger association with hepatic enzyme elevation compared to the other drugs. Conclusions: The study indicates that sodium valproate therapy in children with seizure disorder is associated with significant elevations in liver enzyme levels compared to phenytoin and levetiracetam. Regular liver function monitoring, particularly before and at six-month intervals during sodium valproate therapy, is recommended to detect early signs of hepatotoxicity.